Building sustainable fieldwork partnerships between Canada and India: Finding common goals through evaluation. Issue 1 (2nd January 2018) - Storr, Caroline; MacLachlan, Janna; Krishna, Dinesh; Ponnusamy, Ramasubramanian; Drynan, Donna; Moliner, Carmen; McLaughlin, Kristina; Murphy, Susanne; Edgelow, Megan; Campbell-Rempel, Margaret Anne; Bossers, Ann; Lauckner, Heidi; et al.
ABSTRACT: Initiatives in education and research have taken centre stage to address global health issues. Fieldwork learning in a global context is seen as one strategy to expose students to global health challenges and to collaborate towards viable solutions. Because of the inequities that exist globally, ethical dilemmas can be encountered throughout partnership development and require thoughtful consideration regarding the demands placed on partners in low resourced settings and issues of sustainability. A programme evaluation using the WEIGHT guidelines as a framework for critical reflection discusses the partnership development and future of one collaborative multi-stakeholder programme between Canadian occupational therapy programmes, an Indian partner and a Canadian charity. Collegiality, mentorship and an overall perspective of meeting the WEIGHT guidelines were evident from the reflections. Important considerations of programme equity as it relates to cost, communication and feedback needs, resource gaps and sponsor related issues emerged as areas of future priority.